APPARATUS FOR GENERATING BEADS OF VIRTUAL WELDING TRAINNING SIMULATOR - SHIN, SANG HO; KIM, MAENG NAM; LEE, DONG YOUP; CHO, SUNG HO (2017)
The present invention relates to an apparatus for generating beads of a virtual welding training simulator, capable of generating virtual beads which are similar to real beads in virtual welding training. The apparatus for generating beads of a virtual welding training simulator comprises: a design part designing actual beads by considering actual data according to welding conditions of performing real welding and welding performance results; an input part inputting the actual beads designed in the design part as bead data of virtual welding training; a calculation part calculating shapes of the beads according to welding conditions of performing virtual welding training and welding performance results based on the bead data input from the input part; and an output part visually outputting the shapes of the beads calculated in the calculation part. 본 발명은 가상 용접 훈련 중에 실제와 유사한 가상의 비드를 생성할 수 있는 가상 용접 훈련 시뮬레이터의 비드 생성 장치에 관한 것이다. 본 발명은 실제 용접을 수행하는 용접 조건과 용접 수행 결과에 따른 실측 데이터를 고려하여 실측 비드(bead)를 설계하는 설계부; 상기 설계부에서 설계된 실측 비드를 가상 용접 훈련의 비드 데이터로 입력하는 입력부; 상기 입력부에서 입력된 비드 데이터를 기반으로 현재 가상 용접 훈련을 수행하는 용접 조건 및 용접 수행 결과에 따른 비드의 형태를 산출하는 연산부; 및 상기 연산부에서 산출된 비드의 형태를 시각적으로 출력하는 출력부;를 포함하는 가상 용접 훈련 시뮬레이터의 비드 생성 장치를 제공한다.